Pengaruh Broken Home Terhadap Kesejahteraan Psikologis Anak - Aisha Nabila Khairunnisa; Fadiah Cahyani; Lulu Hardiana; Mutia Nabila Putri; Qurratu Nisaa’Pingatian; Yorisa Rahmawati; Devi Rusli (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the effect of a broken home on children's psychological well-being. A broken home refers to a family condition in which harmony is not maintained, conflicts occur, and may ultimately lead to divorce. Such conditions can affect children's psychological well-being, particularly in terms of their emotional state and personality development. This research employs a literature review method by collecting several articles from online databases such as Google Scholar, published between 2018 and 2022. The selected articles focus on the relationship between broken home conditions and children's psychological well-being. The findings indicate that there is a significant influence of broken home conditions on children's psychological well-being. Children who experience a broken home tend to develop more closed personalities and unstable emotions, which negatively impact their psychological well-being. This study concludes that broken home conditions have an adverse effect on children's psychological well-being.